Laparoscopic resection of retroperitoneal paraganglioma behind the Spiegel lobe in a kyphotic patient: A rare case report. Issue 3 (17th July 2018) - Ogawa, Hisataka; Nakahira, Shin; Kishimoto, Tomoya; Kato, Kazuya; Hasegawa, Makoto; Oyama, Keisuke; Tou, Takayuki; Maki, Ryosuke; Himura, Hoshi; Nishi, Hidemi; Ohhara, Nobuyoshi; Mikami, Jota; et al.
Abstract: Extra‐adrenal paraganglioma is a rare form of neuroendocrine neoplasm capable of catecholamine secretion. The surgical risks associated with the tumor location are compounded in this case of a kyphotic patient. This report presents the successful application of laparoscopy on extra‐adrenal paraganglioma located behind the Spiegel lobe in a kyphotic patient. The operation was performed after 1 week of α‐blocker administration. The laparoscopic approach, with the patient in the left hemilateral decubitus position on a rotating table, provided optimal access for safe tumor resection after complete hepatic right lobe mobilization. The patient's postoperative course was uneventful. Based on the results, the laparoscopic approach can be a safe and effective method for resecting extra‐adrenal paraganglioma in the challenging case of a kyphotic patient.